2014
DOI: 10.1073/pnas.1321576111
|View full text |Cite
|
Sign up to set email alerts
|

Gq/5-HT 2c receptor signals activate a local GABAergic inhibitory feedback circuit to modulate serotonergic firing and anxiety in mice

Abstract: Serotonin 2c receptors (5-HT 2c -Rs) are drug targets for certain mental disorders, including schizophrenia, depression, and anxiety. 5-HT 2c -Rs are expressed throughout the brain, making it difficult to link behavioral changes to circuit specific receptor expression. Various 5-HT-Rs, including 5-HT 2c -Rs, are found in the dorsal raphe nucleus (DRN); however, the function of 5-HT 2c -Rs and their influence on the serotonergic signals mediating mood disorders remain unclear. To investigate the role of 5-HT 2c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 22 publications
3
63
1
Order By: Relevance
“…Of note, one pharmacologic study suggests an anti-depressant effect of MR inhibition (Almeida et al, 2013). Furthermore, increasing DR activity has an anti-depressant effect (Veerakumar et al, 2014; Warden et al, 2012), however the consequence of decreasing DR activity and the contribution of DR 5-HTergic neuronal activity to anxiety behavior still remains controversial (Spoida et al, 2014; Warden et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Of note, one pharmacologic study suggests an anti-depressant effect of MR inhibition (Almeida et al, 2013). Furthermore, increasing DR activity has an anti-depressant effect (Veerakumar et al, 2014; Warden et al, 2012), however the consequence of decreasing DR activity and the contribution of DR 5-HTergic neuronal activity to anxiety behavior still remains controversial (Spoida et al, 2014; Warden et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…These opposing effects of 5HT2c-R antagonism on these two aspects of anxiety may indicate that they are governed by divergent neural circuits. To illustrate this point, a recent study found that optogenetic Gq/5HT2c-R activation of GABAergic interneurons in the DR 5HT2c-Rs actually relieve anxiety in the open field (Spoida et al, 2014), while another study by Breese and colleagues found that a 5HT2c-R inverse agonist (SB 243,213) microinjected into the DR had no effect on CIE induced anxiety in the social interaction test (Overstreet et al, 2006). However, intra-amygdalar injections of SB 243,213 did relieve CIE induced deficits in social interaction, suggesting that 5HT2c-R signaling in the amygdala can modulate the social aspects of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows experimenters to use fiber optic or wireless light-emitting diode technology (Yizhar et al, 2011;Kim et al, 2013) to activate GPCR signaling within selected cell types in the mammalian brain of awake behaving animals. Elegant extensions of this approach have also been used in modifications of vertebrate rhodopsin with components of the 5HT1a or 5HT2c serotonin receptor for examining neural circuits and signaling in anxiety behavior Spoida et al, 2014). Recent work has also shown that chimeric opsin-wild-type receptors can be used to optically mimic opioid receptor signaling (Siuda et al, 2015) (Fig.…”
Section: Tools For In Vivo Gpcr Researchmentioning
confidence: 99%